ทางเลือกในการทำความสะอาดถนนเพื่อลดฝุ่นฟุ้งปลิว - วิฑูรย์ อภิสิทธิ์ภูวกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
To study and compare the dust control efficiency from many different sizes of paved roads by mean of 3 sizes of mechanical road sweepers, washing with water and manual sweeper, to calculate the dust emission rates and estimate cost of option in cleaning street and to recommend suitable method of practice. This research was to choose paved roads of 3 sizes (2, 4 and 6 lanes). There were 2 different study areas, namely Bangkok area and Thunburi area. Bangkok area was cleaned by Bangkok Metropolitan Administration and Thunburi area was cleaned by a private contractor. The number of experimental roads in Bangkok and Thunburi area were 4 and 2 respectively. Dust samples were collected before cleaning to compare with dust samples collected after cleaning 1, 2, 4 and 7 days. The results showed that the street cleaning efficiency by mean of mechanical sweepeers on wide, medium and narrow roads were 30.03%, 58.06% and 70.31% respectively. Street cleaning efficiency by washing with water on wide and narrow roads were 54.79% and 70.09% respectively. Street cleaning efficiency by manual sweeper on medium road was 13.30%. Calculated dust emission rate from moving vehicle, before and after cleaning were between 1.12-4.00 g PM-10/VKT and 0.49-3.11 g PM-10/VKT respectively. The total estimate costs of street cleaning to reduce dust by managing Bangkok Metropolitan Administration were 0.73, 0.54 and 0.52 bath/gram of silt for big, medium and small sweepers, respectively. For washing with water and manual sweeper, the total estimate costs were 0.78 and 5.30 bath/gram of silt respectively. The study showed that the size of mechanical sweepers had no impact on street cleaning efficiency. But street cleaning efficiency varied with size of street. Street cleaning efficiency was best for narrow road and poorest for wide road. Small machine sweeper required the lowest cost of operation. Washing with water was more efficient than mechanical sweeper but it was more expensive. So, washing with water was suitable for dust reducing in more congested streets. Manual sweeper had the lowest street cleaning efficiency but the most expensive costs of street cleaning. However, manual sweepers had to take care of trees and general cleanliness of the area.